Amaryllidaceae Alkaloids of Norbelladine-Type as Inspiration for Development of Highly Selective Butyrylcholinesterase Inhibitors: Synthesis, Biological Activity Evaluation, and Docking Studies - Mamun, Abdullah Al; Pidaný, Filip; Hulcová, Daniela; Maříková, Jana; Kučera, Tomáš; Schmidt, Monika; Catapano, Maria Carmen; Hrabinová, Martina; Jun, Daniel; Múčková, Lubica; Kuneš, Jiří; Janoušek, Jiří; et al. (International journal of molecular sciences, 2021)
Alzheimer's disease (AD) is a multifactorial neurodegenerative condition of the central nervous system (CNS) that is currently treated by cholinesterase inhibitors and the N-methyl-d-aspartate receptor antagonist, memantine. Emerging evidence strongly supports the relevance of targeting butyrylcholinesterase (BuChE) in the more advanced stages of AD. Within this study, we have generated a pilot series of compounds (1-20) structurally inspired from belladine-type Amaryllidaceae alkaloids, namely carltonine A and B, and evaluated their acetylcholinesterase (AChE) and BuChE inhibition properties. Some of the compounds exhibited intriguing inhibition activity for human BuChE (hBuChE), with a preference for BuChE over AChE. Seven compounds were found to possess a hBuChE inhibition profile, with IC50 values below 1 μM. The most potent one, compound 6, showed nanomolar range activity with an IC50 value of 72 nM and an excellent selectivity pattern over AChE, reaching a selectivity index of almost 1400. Compound 6 was further studied by enzyme kinetics, along with in-silico techniques, to reveal the mode of inhibition. The prediction of CNS availability estimates that all the compounds in this survey can pass through the blood-brain barrier (BBB), as disclosed by the BBB score.
Keywords: Tumor Cells, Cultured; Molecular Docking Simulation; cholinesterasové inhibitory; alkaloidy amarylkovitých; vztahy mezi strukturou a aktivitou; simulace molekulového dockingu; Cell Proliferation; Humans; Computer Simulation; Structure-Activity Relationship; Cholinesterase Inhibitors; Tyramine; neuroblastom; tyramin; počítačová simulace; Amaryllidaceae Alkaloids; proliferace buněk; nádorové buňky kultivované; Neuroblastoma; butyrylcholinesterasa; Acetylcholinesterase; lidé; Butyrylcholinesterase; acetylcholinesterasa